Отбор информантов и экспертов при проведении фоностилистических исследований - Шереметьева, Е.В.; Черныш, И.В. (Культура народов Причерноморья, 2014)
Статья посвящена методам социолингвистического и фоностилистического изучения
вариативности произношения, в том числе вопросу выбора участников исследования и проведения
экспериментальных интервью. В статье рассматриваются особенности в организации и методы
проведения фоностилистического исследования, в котором принимается положение о том, что
фонетический стиль является индикатором социальной принадлежности носителя языка. В
исследовании рассмотрен ряд других фоностилистических особенностей произношения носителей
немецкого языка с рождения и носителей немецкого языка как иностранного, обусловленных действием
как внеязыковых, так и языковых факторов.
Эта тема представляет интерес для составления комплексного анализа языковой ситуации в
Германии, так как в настоящее время в Германии проживает большое количество людей, для которых
немецкий язык не является родным языком. Такая тенденция развития социума в Германии
прогнозируется и в ближайшие годы. Стаття присвячена особливостям в підході до залучення учасників для проведення
фоностилістичного дослідження німецької мови, в якому приймається положення про те, що
фонетичний стиль є індикатором соціальної характеристики носія мови. В роботі розглядаються
також інші фоностилістичні особливості вимови носіїв німецької мови від народження та носіїв
німецької мови як іноземної. Ця тема має значення для розробки комплексного аналізу мовної ситуації в
Німеччині. Так, сьогодні в Німеччині мешкає значна кількість вихідців з інших країн світу і ця тенденція
зростає із року в рік. Тому розгляд мовної ситуації в різних макро- й мікросоціумах - це одне з
найважливіших завдань, які стоять перед соціолінгвистикой. The following article dwells on one of the most popular areas of linguistic research. This branch is
called phonostilistics and it is one of the youngest branches of stylistics. Conducting a phonostylistic research
one should pay considerable attention to the selection of informants and experts who will influence the results
substantially. Thus, the author gives perspectives and shares experiences in that area.
One of the main tasks of phonostylistics is a detailed investigation of the phonetic style. The necessity of a
qualitatively new approach in the investigation of this phenomenon as a complex one in interpersonal and
international communication is quite evident. Taking into account the newest tendencies in Germany native
speakers and foreigners must be included in the discussion of the phonetic style problematic.
The aim of this work is the investigation of the phonostylistic variation of spontaneous speech on the basis of the
German language and the reveal of the effect that phonostylistics produces being the speaker’s essential feature.
The task of this investigation also comprises the analysis of phonostylistic peculiarities of the expatriates from
the Eastern and Southern European countries. A number of phenomena somehow connected with the phonetic
style are discussed complexly within this investigation.
The theoretical background of this investigation lies in realization of the phonetic style as a complex phonetic
characteristic of the speech taking into account extralinguistic communicative factors and specific aspects of
phonostylistic variation of foreign speakers’ speech.